Self-destruction and self-exclusion: The suicide in the rural areas of Rio Grande do Sul – Brazil (2014)
This paper deals with suicide in rural areas of Rio Grande do Sul, Brazil, considering the relation of this phenomenon with the advance of the capitalism in the countryside. This change has been creating new living and working styles and, besides, processes which lead to illness. Among these processes, suicide becomes a reality as a process of self-destruction and self-exclusion. These are sociopathologies of the development which are cre-ated in demonstrations of mental illness, depression and suicides, driven by a model of development imposed in the rural area through the economic incentive and, also, through all the economic speech carrying a project of hope. It is about the social and economic systems act-ing as generators of precariousness, human, familiar and psycho-philosophical costs, desocialization processes, self-generated alienation and self-cleaving, showing that it is increasingly necessary to think about the relation between the social and the individual in life and death processes.